Efektifitas Bahan Ajar Buku Panduan Pembelajaran Kebencanaan Di Kabupaten Klaten Pada Bencana Letusan Gunung Berapi Melalui Strategi Talking Stick Di SMKN 1 Klaten - Khanif, Muhammad; , Drs.Suharjo,M.S (2016)
Learning strategies needed to deliver material contained in teaching materials. Strategy is what will be the benchmark for the effectiveness of the teaching materials used. This study aims to 1) determine the effectiveness of teaching materials book "Panduan Pembelajaran Kebencanaan di Kabupaten Klaten" in the eruption of the volcano through a strategy of Talking Stick in SMKN 1 Klaten 2) determine the relationship of the use of teaching materials book "Panduan Pembelajaran Kebencanaan di Kabupaten Klaten" in the eruption of the volcano through the Talking Stick strategy in disaster Preparedness School Extracurricular classes (SSB) and the class of Teaching and Learning Activities (KBM) that does not follow Extracurricular SSB in SMKN 1 Klaten. This type of research used in this study is an experiment, with the Pre Experimental design: One Group Pretest-Posttest Design. The population in this study were students who follow school extracurricular Standby (SSB) Disaster at SMKN 1 Klaten and students who do not follow extracurricular SSB many as 86 students. Assessing the effectiveness of teaching materials book "Panduan Pembelajaran Kebencanaan di Kabupaten Klaten" through a strategy of talking stick is done by comparing the results of the two-class learning Teaching and Learning Activities (KBM) with the same treatment. Two classes are given the same treatment as the present study only tested the effectiveness of teaching materials and not tested the effectiveness of the strategies used. The KBM class consists of classes and class Experiment 1 and Experiment 2, provided pre-test and post-test to determine the increase understanding and knowledge of students. Experiment 2 classes have the ability average grade lower than grade Experiment 1. The results of the t-test showed 0.153> 0.05, which means there are no significant changes between the experimental class 2 and class classroom learning Eksperiment 1. Results were then compared with KBM SSB learning outcomes which became a class Experiment 3. the results of the pre-test and post-test results showed extracurricular SSB better than classroom teaching. Keyword : Effectiveness, teaching materials, talking stick strategy, school disaster preparedness